THE LINGUISTIC ASPECT OF GLOBALIZATION: PERSPECTIVES AND CONSEQUENCES - Hryshyna , N.; Bihari , M. (Theory and Practice of Public Administration, 2020)
Our era is called the era of globalization. This process affects not only the economy; it affects all areas of human life, including language, education, culture, religious preferences, life etc. The analysis proves that English as the main language of globalization and integration processes has recently become very popular in almost all aspects of life in many countries. Of course, this is a positive phenomenon, because knowledge of languages, not only English but also other ones, broadens the horizons, joins the world culture, science, allows to overcome feelings of inferiority due to the inability to communicate with foreign colleagues. Globalization affects any language, it penetrates more and more foreign borrowings, which are thoroughly included in the language of the public sector, economics, science, technology, culture, in the field of domestic and even family communication. At the same time, it is a phenomenon to be positive until English or any language of interethnic communication begins to replace and displace national languages.Summarizing the various literature sources about language policy in different countries, we can identify the following main components: compliance with European principles of language development, continuous improvement of national language legislation, impartial functioning of national institutions for development and state language protection, media space quotas, and active public participation and the general level of national consciousness and culture. Areas for improving these and other components of language policy can be prospects for further research.Ukraine as a part of the world community is also involved in globalization processes in general, and language processes in particular. In addition, our country has found itself in a situation where the processes of Russification are still actual on the one hand, and English and other languages of international communication are gaining ground on the other. At the same time, if the national language is self-sufficient, developed and protected, then globalization and the spread of any language do not threaten it with changes in status characteristics and displacement. And globalization will affect mainly the increase in the number of foreign borrowings, which in the era of globalization has become much more.